Combination of Aloe vera and xenograft induction on decreasing of NF-kb of tooth extraction socket preservation in Cavia cobaya - Utari Kresnoadi; Retno Pudji Rahayu (Universitas Airlangga, 2014)
Background: Tooth extraction can naturally cause inflammation triggering osteoclast proliferation and alveolar bone resorption. Preservation of the tooth extraction sockets is needed for patients in order to reduce alveolar bone resorption risks. Aloe vera is known to have anthraquinones components, namely Aloin, Aloe emedin, and barbaloin, considered as anti-inflammation. Therefore, to overcome the inflammation, the role of NF-kb is very significant to decrease nuclear factor kappa b (NF-kb). As a result, inflammation risks will be decreased. Purpose: The study was aimed to determine the induction effect of combination of Aloe vera and XCB into tooth extraction sockets to reduce inflammation by reducing NF-kb expression, osteoclasts and osteoblasts. Methods: Forty-eight Cavia cobaya were divided into eight groups, each group consisted of six animals. The mandibular incisors of those Cavia cobaya were extracted and induced with either PEG, XCB, Aloe vera, or the combination of Aloe vera + XCB. Those animals were sacrificed on day 7 and day 30 after the extraction. Then immunohistochemical and histopathology examinations were conducted to observe NF-kb expression, osteoblasts and osteoclasts. Results: It was known that in group induced with the combination of Aloe vera and xenograft concelous bovine, the growth of osteoblasts was high, while NF-kb expression and osteoclasts reduced. Conclusion: It can be concluded that the induction of the combination of Aloe vera and XCB into the tooth extraction sockets can reduce NF-kb expression and osteoclast, as a result, alveolar bone resorption risks decrease, and osteoblast increase. <span style="font-family: T